2014
DOI: 10.1093/eurheartj/ehu319
|View full text |Cite
|
Sign up to set email alerts
|

Anacetrapib reduces progression of atherosclerosis, mainly by reducing non-HDL-cholesterol, improves lesion stability and adds to the beneficial effects of atorvastatin

Abstract: The present study is the first intervention study in a well-established, translational mouse model for hyperlipidaemia and atherosclerosis showing that anacetrapib dose-dependently reduces atherosclerosis development and adds to the anti-atherogenic effects of atorvastatin. This effect is mainly ascribed to the reduction in non-HDL-C despite a remarkable increase in HDL-C and without affecting HDL functionality. In addition, anacetrapib improves lesion stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 42 publications
4
55
1
Order By: Relevance
“…Similarly as in familial dyslipoproteinemia patients, in E3L and E3L.CETP mice as a model for mixed dyslipoproteinemia, a major part of plasma cholesterol is contained in the VLDL (remnant) particles, leading to the formation of ␤ -VLDL particles, which further increases after cholesterol feeding. The E3L.CETP mouse model, unlike Apoe Ϫ / Ϫ and Ldlr Ϫ / Ϫ mice, responds in a human-like way to the lipid-lowering effects of statins ( 18 ), fi brates ( 19 ), niacin ( 20,21 ), torcetrapib ( 15 ), anacetrapib ( 22 ), and antiPCSK9mabs ( 23 ), with respect to both direction and magnitude of the change. In conclusion, E3L.CETP mice have a more human-like lipoprotein metabolism when compared with C57Bl/6, Apoe…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly as in familial dyslipoproteinemia patients, in E3L and E3L.CETP mice as a model for mixed dyslipoproteinemia, a major part of plasma cholesterol is contained in the VLDL (remnant) particles, leading to the formation of ␤ -VLDL particles, which further increases after cholesterol feeding. The E3L.CETP mouse model, unlike Apoe Ϫ / Ϫ and Ldlr Ϫ / Ϫ mice, responds in a human-like way to the lipid-lowering effects of statins ( 18 ), fi brates ( 19 ), niacin ( 20,21 ), torcetrapib ( 15 ), anacetrapib ( 22 ), and antiPCSK9mabs ( 23 ), with respect to both direction and magnitude of the change. In conclusion, E3L.CETP mice have a more human-like lipoprotein metabolism when compared with C57Bl/6, Apoe…”
Section: Methodsmentioning
confidence: 99%
“…ANCOVA showed that the effect on lesion size was mainly explained by a reduction in (V)LDL-C ( 22 ). However, the mechanism by which anacetrapib reduces plasma (V)LDL-C and TG is not fully understood.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, serum SAA levels were increased by the treatment of anacetrapib and atorvastatin in APOE*3Leiden.CETP mice (33). It is important to know whether the inflammation is correlated with any of HDL function and what is the mechanism inhibiting antioxidant activity of HDL when CETP inhibitors are used.…”
Section: Hdl Function and Anti-inflammatory Effects In Cetp Deficiencmentioning
confidence: 99%